Pendataan dan Penyaluran Bantuan Langsung Tunai Dana Desa Penanggulangan Covid 19 oleh Pemerintah Desa Di Kecamatan Depati VII Kabupaten Kerinci - M Muslih; Herma Yanti (Universitas Batanghari Jambi, 2021)
The data collection and distribution of the Village Fund Direct Cash Assistance (BLT) by the Village Head is the implementation of the Central Government program in order to help ease the economic burden of the poor who are affected by the Covid-19 outbreak. The data collection and distribution of Village Funds is carried out through the respective Village Heads so that the assistance can be distributed smoothly and on target according to the goals that have been set, including in the District of Depati VII, Kerinci Regency. However, in its implementation, data collection and distribution activities are in the spotlight because there are discrepancies with the expected goals. Therefore, this study aims to further discuss the implementation of data collection and distribution of the Village Fund BLT Fund in the District of Depati VII, Kerinci Regency and the problems encountered in it.